MESH CONVERGENCE TEST BY USING FINITE ELEMENT ANALYSIS (FEA) IN SHAFT LOADING OF 2 KW INDUCTION MOTOR - Hotma, Lambert; Majid, Nur Cholis; Marsalyna; Hendrawan , Jekki; Kinasih, Nirma Afrisanti; Febriansyah, Dwi Jaya; Novariawan , Bayu; Alfin , Muhammad Reza; Putri, Intan Satwika; Ghufron, Hanif; Afif, Muhammad Thowil; Fadjrin, Budi Noviyantoro; Purnomo , Endra Dwi (Jurnal Rekayasa Mesin, 2024)
Finite Element Analysis (FEA) is a calculation tool to find out a determined solution for a complex structure subjected to some certain static load. To obtain the most valid solution from this analysis, one of the parameters needed is mesh convergence test. This paper discusses the mesh convergence test by using FEA in a 2-kW induction motor shaft where the motor is used in an electric motorcycle. FEA was carried out by using static structural module in ANSYS 14.5 software. The shaft was subjected to static load from rotor and pulley weight. These loads were supported by a pair of ball bearing. Furthermore, the shaft was meshed by using various sizes of mesh to find out the effects to mesh convergence. The applied mesh sizes were 3; 2,5; 2; 1,5; and 1 mm. These simulation results represented the value of deformation and stress on the shaft. The convergence test was depicted in a graph of elements number vs. deformation and elements number vs. Von – Mises stress. The maximum deformation was located around rotor seat, while the minimum one was around the rear bearing seat. On the other hand, maximum and minimum Von – Mises stress appeared around rear bearing seat. Overall, it can be concluded that the results of deformation and Von – Mises stress had reached convergence